2021
DOI: 10.1002/brb3.2446
|View full text |Cite
|
Sign up to set email alerts
|

Negative valence of hallucinatory voices as predictor of cortical glutamatergic metabolite levels in schizophrenia patients

Abstract: Objectives Negative emotional valence of auditory verbal hallucinations (AVHs) in schizophrenia can be a source of distress and is considered a strong predictor of illness severity. Previous studies have found glutamate to mediate AVH severity in frontal and temporal brain regions, however, they do not specifically address emotional valence of AVH. The role of glutamate for the experience of negative‐ versus positive emotional valence of AVH is therefore unknown and was investigated in the current study. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…To date however, no studies have examined the relationship between E/I balance (GABA and glutamate metabolite concentrations) and GMV in an adult CT population. In the current study, because CT is a major risk factor for depression, anxiety and psychosis ( Green et al, 2010 ; Paus et al, 2008 ; Varese et al, 2012 ), we chose to examine glutamate and GABA concentrations in the left STG as an altered function, perfusion or structure in this region is one of the most robust neuroimaging findings in these populations (see Allen et al, 2019 ; Arnone et al, 2016 ; Madonna et al, 2019 ; Scheepens et al, 2020 ), and changes in temporal lobe metabolite concentrations have been reported in these populations ( Hjelmervik et al, 2022 ; Hugdahl et al, 2015 ; Trzesniak et al, 2008 ; Venkatraman et al, 2009 ). In the current study, we aimed to compare left STG GABA and glutamate, as well as whole-brain and left STG GMV in young adults with high and low levels of CT. We predicted that, relative to participants with low CT, a high CT group would show reduced glutamate and GABA concentrations and GMV in the left STG.…”
Section: Introductionmentioning
confidence: 99%
“…To date however, no studies have examined the relationship between E/I balance (GABA and glutamate metabolite concentrations) and GMV in an adult CT population. In the current study, because CT is a major risk factor for depression, anxiety and psychosis ( Green et al, 2010 ; Paus et al, 2008 ; Varese et al, 2012 ), we chose to examine glutamate and GABA concentrations in the left STG as an altered function, perfusion or structure in this region is one of the most robust neuroimaging findings in these populations (see Allen et al, 2019 ; Arnone et al, 2016 ; Madonna et al, 2019 ; Scheepens et al, 2020 ), and changes in temporal lobe metabolite concentrations have been reported in these populations ( Hjelmervik et al, 2022 ; Hugdahl et al, 2015 ; Trzesniak et al, 2008 ; Venkatraman et al, 2009 ). In the current study, we aimed to compare left STG GABA and glutamate, as well as whole-brain and left STG GMV in young adults with high and low levels of CT. We predicted that, relative to participants with low CT, a high CT group would show reduced glutamate and GABA concentrations and GMV in the left STG.…”
Section: Introductionmentioning
confidence: 99%